2016
DOI: 10.1093/gerona/glw048
|View full text |Cite
|
Sign up to set email alerts
|

A Stress-Resistant Lipidomic Signature Confers Extreme Longevity to Humans

Abstract: Plasma lipidomic profile is species specific and an optimized feature associated with animal longevity. In the present work, the use of mass spectrometry technologies allowed us to determine the plasma lipidomic profile and the fatty acid pattern of healthy humans with exceptional longevity. Here, we show that it is possible to define a lipidomic signature only using 20 lipid species to discriminate adult, aged and centenarian subjects obtaining an almost perfect accuracy (90%-100%). Furthermore, we propose sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 35 publications
1
56
0
3
Order By: Relevance
“…Longer lifespans were also correlated with a higher average fatty acid chain length. The authors also proposed that specific lipid species of ceramides are biomarkers of extreme longevity (Jove et al, ). Even more recently, Wong et al have used lipidomics to discover that their “oldest old” subjects over 95 years of age exhibited globally low levels of lipids.…”
Section: Lipid Biomarkers Of Aging In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…Longer lifespans were also correlated with a higher average fatty acid chain length. The authors also proposed that specific lipid species of ceramides are biomarkers of extreme longevity (Jove et al, ). Even more recently, Wong et al have used lipidomics to discover that their “oldest old” subjects over 95 years of age exhibited globally low levels of lipids.…”
Section: Lipid Biomarkers Of Aging In Humansmentioning
confidence: 99%
“…Two of these papers reported that human longevity is associated with lower unsaturated fatty acid content (Gonzalez‐Covarrubias et al, ; Jove et al, ) and two different studies identified sex‐specific age differences in lipid content (Gonzalez‐Covarrubias et al, ; Wong et al, ). All three studies linked sphingolipids to aging (Gonzalez‐Covarrubias et al, ; Jove et al, ; Wong et al, ). Broader lipidomic screens are warranted to better understand additional plasma lipids that with age and how plasma lipids uniquely change for men and women.…”
Section: Lipid Biomarkers Of Aging In Humansmentioning
confidence: 99%
“…The essential mechanistic role of lipid metabolism and transport in defining longevity of this unicellular eukaryote further supports the notion that some aspects of the maintenance of lipid homeostasis are essential for healthy aging in evolutionarily distant organisms. These eukaryotic organisms include not only laboratory strains of budding yeast, roundworms (15,, fruit flies (214)(215)(216)(217)(218)(219)(220)(221)(222)(223) and mammals (208,(224)(225)(226)(227)(228)(229)(230)(231)(232)(233)(234)(235)(236)(237)(238)(239)(240)(241), but also humans (208,(232)(233)(234)(235)(241)(242)(243)(244)(245)(246). The major challenge now is to get a greater insight into the mechanisms through which lipid metabolism and transport define lifespan and healthspan in multicellular model organisms and humans.…”
Section: Summary and Perspectivementioning
confidence: 99%
“…To this diversity in spatial distribution must be added the temporal factor. Thus, the lipid profile varies in time according with a circadian rhythmicity (Aviram et al, 2016), as well as during the life cycle of an organism (Naudí et al, 2015; Jové et al, 2017). …”
Section: Introductionmentioning
confidence: 99%